2013
DOI: 10.4049/jimmunol.1300501
|View full text |Cite
|
Sign up to set email alerts
|

Y14 Positively Regulates TNF-α–Induced NF-κB Transcriptional Activity via Interacting RIP1 and TRADD Beyond an Exon Junction Complex Protein

Abstract: Although Y14 is known to be a component of the exon junction complex, we previously reported that Y14 regulates IL-6–induced STAT3 activation. In this study, we showed that endogenous Y14 positively regulated TNF-α–induced IL-6 expression in HeLa cells. Small interfering RNA–mediated Y14-knockdown reduced TNF-α–induced and NF-κB–mediated transcriptional activity, phosphorylation/degradation of IκBα, and nuclear localization of NF-κB/p65. As in the case of IL-6 stimuli, Y14 enhanced TNF-α–induced STAT3 phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Ras/MAPK, JAK/STAT3 and NF-κB signaling pathways are confirmed to be closely related to occurrence, development, invasion and metastasis of liver cancer (25)(26)(27). Loss of RBM8A led to changes of all these signaling pathways (23,(28)(29)(30): loss of RBM8A led to reduction of MAPK protein and inhibited Ras/MAPK signaling pathway which resulted in cell apoptosis; loss of RBM8A resulted in inhibition of JAK/ STAT3 signaling pathway and prohibited bindings between DNA and STAT3; loss of RBM8A also led to decrease of phosphorylation of TNF-α/STAT3 signaling pathway and reduced the effect of NF-κB. As a common factor of these three signaling pathways, RBM8A protein plays vital roles in inhibiting cell growth and apoptosis.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Ras/MAPK, JAK/STAT3 and NF-κB signaling pathways are confirmed to be closely related to occurrence, development, invasion and metastasis of liver cancer (25)(26)(27). Loss of RBM8A led to changes of all these signaling pathways (23,(28)(29)(30): loss of RBM8A led to reduction of MAPK protein and inhibited Ras/MAPK signaling pathway which resulted in cell apoptosis; loss of RBM8A resulted in inhibition of JAK/ STAT3 signaling pathway and prohibited bindings between DNA and STAT3; loss of RBM8A also led to decrease of phosphorylation of TNF-α/STAT3 signaling pathway and reduced the effect of NF-κB. As a common factor of these three signaling pathways, RBM8A protein plays vital roles in inhibiting cell growth and apoptosis.…”
Section: Discussionmentioning
confidence: 88%
“…RBM8A is found highly expressed in malignant tumors such as primary liver cancer, pleural endotheliomas, multiple myeloma and other malignant tumors (3,11,12,(20)(21)(22)(23). Further analysis revealed that the function of RBM8A could be that the knockdown of RBM8A in lung adenocarcinoma resulted in cell cycle arrest in G2/M phase.…”
Section: Discussionmentioning
confidence: 99%
“…RBM8A is an RNA recognition motif-containing protein that forms heterodimers with MAGOH and serves as a core factor of the RNA surveillance machinery for the exon junction complex. RBM8A is known to be a component of the exon junction complex, which could regulate IL-6-induced STAT3 activation in human cervix carcinoma cell line (17). RBM8A-deficient cells cannot enter the next G1 phase beyond G2/M phase after release from G1/S arrest (9).…”
Section: Discussionmentioning
confidence: 99%
“…The synthesized FLAG‐tagged LMP1 4xANTD mutant was obtained from GenScript (Piscataway, NJ, USA). STAT3‐LUC and NF‐κB‐LUC were kindly provided by T. Hirano (Osaka University Medical School, Osaka, Japan) and T. Fujita (Kyoto University, Kyoto, Japan) . Anti‐FLAG antibody was purchased from Sigma‐Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%